A comprehensive DFT study to evaluate the modulation in the band gap, elastic, and optical behaviour of CsPbBr3 under the effect of stress. (1st December 2022) - Zaidi, S M Junaid; Khan, M Ijaz; Gillani, S S A; Sahar, M Sana Ullah; Ullah, Sana; Tanveer, Muhammad
Abstract: The computational Generalized Gradient Approximations (GGA) are applied on cubic Cesium Lead Bromide (CsPbBr3 ) with different stress values of 0, 5, 10, and 15 GPa for a supercell with PBE exchange relationship parameters to study the structural, mechanical, and optoelectronic characteristics. This study aims to determine how stress affects structural and electronic properties, how optical behaviour changes in reaction to electronic change, and how mechanical properties change as a result. The structure remains cubic, and there is no phase shift, but a reduction in the lattice parameters is seen. The reduction in band gap (1.900 eV) is found from 0–15 GPa and zero at 17 GPa. The partial densities of states (PDOS) of bulk CsPbBr3, Cs, Pb, and Br are also calculated. The partial density states PDOS of bulk CsPbBr3 show that in the valence band range, the sharpest observed peak is for d -states, while in the conduction region, the sharpest peak is for p -states and then for s -states. The significant variation in values of absorption, conductivity (imaginary and real), dielectric function (imaginary and real), loss function, reflectivity, and refractive index (imaginary and real) are found by applying stresses of 0, 5, 10, 15 GPa. Using the energy deformation relationship, the elastic constants are computed. From these constants, various mechanical characteristics such as the bulk modulus, shear modulus, Young modulus, and Poisson ratio are derived and discussed. Additionally, it is a good component in optoelectronic devices due to its high refractive index, absorption, reflectivity, and conductivity.